Carbonaceous-coated graphite particles, negative electrode for lithium ion secondary batteries, lithium ion secondary battery, and method for producing carbonaceous-coated graphite particles

By performing carbon-based coating on the surface of graphite particles and optimizing the firing conditions, a specific crystalline carbon-based coating graphite particles is formed, which solves the problem of insufficient retention of graphite particles in the prior art, and significantly improves lithium ion two Battery characteristics of secondary batteries.

CN119317597APending Publication Date: 2025-01-14JFE CHEMICAL CORP +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202480002872.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-03-06
Filing Date
2024-02-28
Publication Date
2025-01-14

AI Technical Summary

Technical Problem

When the conventional graphite particles are used as the negative electrode material of lithium-ion secondary battery, the circulation capacity retention is insufficient, resulting in poor battery characteristics.

Method used

By performing carbonaceous coating on the surface of graphite particles, the firing conditions are optimized to form carbonaceous coated graphite particles with specific crystallinity, and these carbonaceous coated graphite particles are used as the negative electrode material in lithium-ion secondary batteries.

Benefits of technology

The circulation capacity retention and initial charge and discharge characteristics of lithium-ion secondary batteries are significantly improved, and the overall performance of the battery is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005166475430000191
    Figure BDA0005166475430000191
  • Figure HDA0005166475440000011
    Figure HDA0005166475440000011
Patent Text Reader

Abstract

Provided are carbonaceous-coated graphite particles having excellent cycle capacity retention when used as a negative electrode material for a lithium ion secondary battery. The carbonaceous-coated graphite particles comprise graphite particles and a carbonaceous coating at least a portion of the surface of the graphite particles, and the modulus of elasticity of the carbonaceous-coated graphite particles as determined using a scanning probe microscope is 10 GPa or more.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to carbonaceous coated graphite particles, a negative electrode for a lithium ion secondary battery, a lithium ion secondary battery and a method for producing the carbonaceous coated graphite particles. Background Art

[0002] A lithium-ion secondary battery has a negative electrode, a positive electrode, and a non-aqueous electrolyte as main components, and functions as a secondary battery by allowing lithium ions to move between the negative electrode and the positive electrode during discharge and charge processes.

[0003] Conventionally, spheroidized graphite particles (spheroidized graphite) have been used as negative electrode materials for lithium ion secondary batteries (Patent Document 1).

[0004] Prior art literature

[0005] Patent Literature

[0006] Patent Document 1: Japanese Patent Application Publication No. 2014-146607 Summary of the invention

[0007] Problems to be solved by the invention

[0008] If conventional graphite particles (for example, spheroidized graphite) are used as negative electrode materials for lithium ion secondary batteries, battery characteristics such as cycle capacity retention may be insufficient.

[0009] As a result of the research, the present inventors have found that the battery characteristics can be improved by using carbon-coated graphite particles in which the surfaces of graphite particles are coated with carbon.

[0010] Therefore, an object of the present invention is to provide carbonaceous coated graphite particles which are excellent in cycle capacity retention when used as a negative electrode material for a lithium ion secondary battery.

[0011] Solutions to the problem

[0012] As a result of intensive studies, the present inventors have found that carbonaceous material having specific crystallinity can be obtained by optimizing the calcination conditions when producing carbonaceous coated graphite particles. As a result, the above-mentioned object can be achieved, thereby completing the present invention.

[0013] That is, the present invention provides the following [1] to [7].

[0014] [1] A carbonaceous coated graphite particle comprising:

[0015] Graphite particles, and

[0016] a carbonaceous material covering at least a portion of the surface of the graphite particles;

[0017] The elastic modulus of the carbonaceous coated graphite particles measured using a scanning probe microscope is 10 GPa or more.

[0018] [2] The carbonaceous coated graphite particles according to [1] above, wherein the particle size is 5.0 to 15.0 μm and the specific surface area is 3.0 to 15.0 m 2 / g.

[0019] [3] The carbonaceous coated graphite particles according to [1] or [2] above, wherein

[0020] The content of the carbonaceous material is 1.0 to 30.0% by mass relative to the total mass of the carbonaceous coated graphite particles.

[0021] [4] The carbonaceous coated graphite particles according to any one of [1] to [3] above, which are a negative electrode material for a lithium ion secondary battery.

[0022] [5] A negative electrode for a lithium ion secondary battery, comprising the carbonaceous coated graphite particles according to any one of [1] to [3] above.

[0023] [6] A lithium ion secondary battery comprising the negative electrode described in [5] above.

[0024] [7] A method for producing carbonaceous coated graphite particles, the method being a method for producing the carbonaceous coated graphite particles described in any one of [1] to [3] above, the method comprising:

[0025] making a carbonaceous precursor, which is a precursor of the carbonaceous material, adhere to the graphite particles to obtain precursor-attached graphite particles,

[0026] A first calcination step is performed in which the precursor-attached graphite particles are heated at a temperature exceeding 900° C. and not more than 1500° C. in a non-oxidizing gas atmosphere.

[0027] After the first calcination, an intermediate exposure is performed in which the precursor-attached graphite particles are exposed to an oxidizing gas atmosphere at a temperature of 50 to 100° C.

[0028] After the intermediate exposure, a second calcination is performed in which the precursor-attached graphite particles are heated at a temperature of 1100 to 1500° C. in a non-oxidizing gas atmosphere.

[0029] Effects of the Invention

[0030] According to the present invention, it is possible to provide carbonaceous coated graphite particles having excellent cycle capacity retention when used as a negative electrode material for a lithium ion secondary battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1This is a cross-sectional view of an evaluation battery produced to evaluate battery characteristics in Examples and Comparative Examples.

[0032] Explanation of symbols

[0033] 1: External cup

[0034] 2: Negative electrode

[0035] 3: External can

[0036] 4: Positive electrode

[0037] 5: Partition

[0038] 6: Insulation pad

[0039] 7a: Current Collector

[0040] 7b: Current collector DETAILED DESCRIPTION

[0041] In this specification, when "to" is used to express a range, the range includes both ends of "to". For example, the range of A to B includes A and B.

[0042] [Carbon coated graphite particles]

[0043] The carbonaceous coated graphite particles of the present embodiment (hereinafter also referred to as "the present carbonaceous coated graphite particles") comprise graphite particles and carbonaceous material coating at least a portion of the surface of the graphite particles, wherein the elastic modulus of the carbonaceous coated graphite particles measured using a scanning probe microscope is 10 GPa or more.

[0044] When the present carbonaceous coated graphite particles are used as a negative electrode material for a lithium ion secondary battery, the cycle capacity retention is excellent.

[0045] 〈Elastic modulus〉

[0046] For the present carbonaceous coated graphite particles, for the reason of excellent cycle capacity retention, the elastic modulus (hereinafter also referred to as "elastic modulus") obtained using a scanning probe microscope (SPM) is 10 GPa or more, preferably 12 GPa or more, further preferably 14 GPa or more, and particularly preferably 16 GPa or more.

[0047] The reason for the excellent cycle capacity retention is not clear, but it can be speculated that when the elastic modulus does not satisfy the above range, the carbonaceous material covering the surface of the graphite particles is insufficient, while when the elastic modulus is within the above range, the carbonaceous material sufficiently covers the surface of the graphite particles.

[0048] On the other hand, the elastic modulus of the carbonaceous coated graphite particles is preferably 25 GPa or less, more preferably 24 GPa or less, and even more preferably 22 GPa or less, because of excellent rapid charging characteristics.

[0049] The measurement of the elastic modulus using a scanning probe microscope (SPM) was performed as follows.

[0050] First, epoxy resin was thinly applied to a silicon substrate, and the sample (carbonaceous coated graphite particles) was spread and fixed thereon. Then, the probe was scanned along the particle surface under the following conditions (for each particle, the pressure load was 200nN) to obtain a force curve. The obtained force curve was fitted with a DMT model to obtain the elastic modulus of each particle (monomer: GPa). The average value of the obtained elastic modulus was obtained as the elastic modulus of the sample (carbonaceous coated graphite particles).

[0051] ·SPM: Dimension ICON (manufactured by Bruker)

[0052] ·SPM controller: Nano Scope V (Bruker)

[0053] Probe: Silicon cantilever (manufactured by Bruker)

[0054] Probe (cantilever) specifications: Single crystal Si, curvature radius 8nm

[0055] ·Measurement range: 2μm×2μm

[0056] ·Number of measurements: 512×512 points

[0057] ·Measurement mode: QNM Scan mode (mode for measuring shape and elastic modulus)

[0058] ·Measurement gas atmosphere: Argon atmosphere

[0059] 〈Carbon content〉

[0060] The carbon content is preferably 1.0 mass % or more, more preferably 3.0 mass % or more, further preferably 3.5 mass % or more, particularly preferably 4.5 mass % or more, relative to the total mass of the carbonaceous coated graphite particles.

[0061] When the carbon content is within this range, active edge surfaces of graphite particles are easily covered, and the initial charge and discharge characteristics are excellent.

[0062] On the other hand, the carbon content is preferably 30.0 mass % or less, more preferably 25.0 mass % or less, further preferably 20.0 mass % or less, further preferably 15.0 mass % or less, particularly preferably 10.0 mass % or less, and most preferably 8.0 mass % or less.

[0063] When the content of carbonaceous materials is within the above range, the amount of carbonaceous materials having relatively low discharge capacity decreases, and the discharge capacity is excellent.

[0064] When the carbonaceous content is within this range, the amount of the carbonaceous precursor to be described later is reduced, so that fusion is less likely to occur during mixing and firing described later, and cracking and peeling of the finally obtained carbonaceous material can be suppressed, resulting in excellent initial charge and discharge characteristics.

[0065] The carbon content may be any content as long as the average value of the entire carbonaceous coated graphite particles is within the above range. It is not necessary for all carbonaceous coated graphite particles to be within the above range, and some carbonaceous coated graphite particles outside the above range may be included.

[0066] Only the carbonaceous precursor was fired under the same conditions as those for firing the precursor-attached graphite particles described later, and the carbonaceous content was determined from the residual carbon content.

[0067] Hereinafter, for convenience, the content of carbonaceous material relative to the total mass of carbonaceous-coated graphite particles may be simply referred to as “the content of carbonaceous material”.

[0068] 〈Particle size〉

[0069] The particle size of the carbonaceous coated graphite particles is preferably 5.0 μm or more, more preferably 6.0 μm or more, and even more preferably 6.5 μm or more.

[0070] On the other hand, the particle size of the present carbonaceous coated graphite particles is preferably 15.0 μm or less, more preferably 12.0 μm or less, further preferably 10.0 μm or less, and particularly preferably 9.0 μm or less.

[0071] The particle size is a median diameter at which the cumulative frequency of the particle size distribution determined using a laser diffraction particle size distribution analyzer (LMS2000e, manufactured by Seishin Enterprise Co., Ltd.) is 50% in terms of volume percentage.

[0072] 〈Specific surface area〉

[0073] The specific surface area of ​​the carbonaceous coated graphite particles is preferably 3.0 m 2 / g or more, more preferably 4.0m 2 / g or more, more preferably 4.5m 2 / g or more, particularly preferably 4.0m 2 / g or above.

[0074] On the other hand, the specific surface area of ​​the carbonaceous coated graphite particles is preferably 20.0 m 2 / g or less, more preferably 18.0m 2 / g or less, more preferably 15.0m 2 / g or less, particularly preferably 14.5m 2 / g or less.

[0075] The specific surface area is determined by the BET method, and more specifically, by nitrogen adsorption in accordance with JIS Z 8830:2013 (method for measuring specific surface area of ​​powders (solids) by gas adsorption).

[0076] [Method for producing carbonaceous coated graphite particles]

[0077] Next, a method for producing carbonaceous coated graphite particles according to the present embodiment (hereinafter also referred to as “the present production method”) will be described.

[0078] The present production method is a method for producing the present carbonaceous coated graphite particles described above. In summary, a carbonaceous precursor is attached to graphite particles, and then first calcination, intermediate exposure, and second calcination (hereinafter collectively referred to as "calcination") described below are sequentially performed.

[0079] Hereinafter, first, the graphite particles and the carbonaceous precursor used in the present production method will be described, and then each step in the present production method will be described.

[0080] 〈Graphite Particles〉

[0081] The method for producing the graphite particles used in the present production method is not particularly limited, and an example thereof includes a method of processing a raw material into a spherical shape.

[0082] Here, the raw material is graphite having a shape other than spherical (including ellipsoidal), for example, flaky graphite. The graphite may be either natural graphite or artificial graphite, but natural graphite is preferred because of its high crystallinity.

[0083] Specific examples of methods for processing the raw material into a spherical shape (method for spheronizing the raw material) include: a method of stirring the raw material in the presence of a granulation aid such as a binder or resin; a method of applying a mechanical external force to the raw material without using a granulation aid; a method of using both in combination, and the like.

[0084] Among them, a method of applying a mechanical external force to the raw material without using a granulation aid is preferred. This method will be described in more detail below.

[0085] More specifically, a raw material (for example, flaky graphite) is pulverized and granulated by applying a mechanical external force using a pulverizing device, thereby spheroidizing the raw material to obtain spheroidized graphite.

[0086] Examples of the pulverizing apparatus include a rotary ball mill, a counter jet mill (manufactured by Hosokawa Micron Co., Ltd.), a Current Jet (manufactured by Nisshin Engineering Co., Ltd.), a Hybridization System (manufactured by Nara Machinery Manufacturing Co., Ltd.), a CF pulverizer (manufactured by Ube Industries, Ltd.), a Mechano Fusion System (manufactured by Hosokawa Micron Co., Ltd.), and a THETA COMPOSER (manufactured by Tokuju Kosho Co., Ltd.). Among them, the Hybridization System (manufactured by Nara Machinery Manufacturing Co., Ltd.) is preferred.

[0087] In the present production method, it is preferred that a plurality of pulverizing devices are arranged in series and the raw material is continuously passed through the plurality of pulverizing devices. That is, it is preferred that the plurality of pulverizing devices are arranged in series so that the raw material is immediately pulverized and granulated in the next pulverizing device after passing through one pulverizing device.

[0088] In this case, the number of pulverizing devices is, for example, 2 or more, preferably 3 or more, more preferably 4 or more, further preferably 5 or more, particularly preferably 6 or more.

[0089] On the other hand, the number of pulverizing devices is preferably 10 or less, more preferably 8 or less, and even more preferably 7 or less.

[0090] In one pulverizing device, the time for pulverizing and granulating the raw material (hereinafter also referred to as "pulverizing time") is preferably 8 minutes or more, more preferably 13 minutes or more, and even more preferably 18 minutes or more.

[0091] On the other hand, the pulverization time of one pulverization device is preferably 60 minutes or less, more preferably 50 minutes or less, and even more preferably 40 minutes or less.

[0092] The product of the number of pulverizing devices and the pulverizing time of one pulverizing device (hereinafter also referred to as "total pulverizing time") is preferably 30 minutes or more, more preferably 50 minutes or more, and even more preferably 90 minutes or more.

[0093] On the other hand, the total pulverization time is preferably 180 minutes or less, more preferably 160 minutes or less.

[0094] The pulverizing device usually has a built-in rotor.

[0095] The peripheral speed of the rotor in each pulverizing device is preferably 30 m / sec or more, more preferably 40 m / sec or more, and even more preferably 60 m / sec or more.

[0096] On the other hand, the peripheral speed of the rotor in each pulverizing device is preferably 100 m / sec or less, more preferably 80 m / sec or less.

[0097] In order to apply shearing force and compressive force to the raw material, the amount of the raw material filled in each pulverizing device is preferably small.

[0098] 〈Carbonaceous Precursor〉

[0099] The carbonaceous precursor is the precursor of the carbonaceous material described above, and is carbonized by the calcination described later to become the carbonaceous material covering the graphite particles.

[0100] Examples of the carbonaceous precursor include resins, which are carbon materials having lower crystallinity than graphite and which do not turn into graphite crystals even when subjected to a high-temperature treatment required for graphitization.

[0101] Examples of the resins include polyvinyl alcohol, polyacrylic acid, phenol resin, furan resin, cellulose resin, polystyrene resin, polyimide resin, and epoxy resin.

[0102] From the viewpoint of battery characteristics of the obtained battery, phenol resin is preferred.

[0103] In order to easily spread on the surface of graphite particles, the carbonaceous precursor is preferably in powder form. The median particle size (D 50 ) is not particularly limited, and is, for example, 1 to 50 μm.

[0104] 〈Preparation of Precursor-Attached Graphite Particles〉

[0105] In the present production method, first, a carbonaceous precursor is made to adhere to graphite particles, thereby obtaining precursor-adhered graphite particles in which the carbonaceous precursor adheres to at least a portion of the surface of the graphite particles.

[0106] As a method of making the carbonaceous precursor adhere to the graphite particles, a method of mixing the graphite particles and the carbonaceous precursor is mentioned, for example.

[0107] The mixing method is not particularly limited, and an example thereof includes a method of mixing graphite particles with a powdered or heated and melted carbonaceous precursor in a liquid state using a mixer or the like. In this case, a dispersion obtained by dispersing graphite particles in a dispersion medium may be used. Examples of the mixer include a pressure kneading machine, a double-roll mixer, and the like.

[0108] 《Amount of carbonaceous precursor added》

[0109] The amount of the carbonaceous precursor added (the amount of the carbonaceous precursor attached to the graphite particles) can be appropriately adjusted according to the desired amount of carbonaceous material to be finally obtained.

[0110] 〈Firing〉

[0111] Next, the obtained precursor-attached graphite particles are subjected to calcination (first calcination, intermediate exposure, and second calcination). Thus, the carbonaceous precursor is carbonized to form a carbonaceous material.

[0112] Thus, carbonaceous-coated graphite particles in which at least a part of the surface of the graphite particles is coated with carbon are obtained. The elastic modulus of the obtained carbonaceous-coated graphite particles satisfies the above-mentioned range.

[0113] 《First Firing》

[0114] In the first calcination, the precursor-adhered graphite particles are heated at a temperature exceeding 900° C. and not more than 1500° C. (hereinafter also referred to as “first calcination temperature”) in a non-oxidizing gas atmosphere.

[0115] The reason why the gas atmosphere of the first firing is set to a non-oxidizing gas atmosphere is that carbonaceous materials burn and disappear in an oxidizing gas atmosphere.

[0116] Examples of the non-oxidizing gas atmosphere include nitrogen atmosphere, argon atmosphere, helium atmosphere, and vacuum atmosphere. The oxygen concentration of the gas atmosphere may be reduced by placing coke dust that oxidizes itself, thereby substantially providing a non-oxidizing gas atmosphere.

[0117] The first calcination temperature exceeds 900° C., preferably 950° C. or higher, and more preferably 1000° C. or higher. On the other hand, the first calcination temperature is 1500° C. or lower, preferably 1400° C. or lower, and more preferably 1250° C. or lower.

[0118] The time for implementing the first calcination (the time for heating the precursor attached graphite particles at the first calcination temperature in a non-oxidizing gas atmosphere) is preferably 0.5 hours or more, more preferably 1 hour or more, and further preferably 2 hours or more. The upper limit is not particularly limited, for example, 30 hours, preferably 10 hours, and more preferably 5 hours.

[0119] The precursor-attached graphite particles after the first calcination are preferably cooled directly in the gas atmosphere of the first calcination (non-oxidizing gas atmosphere) to the intermediate exposure temperature described later.

[0120] "Intermediate Exposure"

[0121] In the intermediate exposure, the precursor-adhered graphite particles that have been subjected to the first calcination (and then cooled) are exposed to an oxidizing gas atmosphere at a temperature of 50 to 100° C. (hereinafter also referred to as “intermediate exposure temperature”).

[0122] Examples of the oxidizing gas atmosphere include a gas atmosphere containing oxygen, ozone, and carbon dioxide, and an air atmosphere is preferred from the viewpoint of convenience.

[0123] The intermediate exposure temperature is 50° C. or higher, preferably 55° C. or higher, and more preferably 60° C. or higher. On the other hand, the intermediate exposure temperature is 100° C. or lower, preferably 90° C. or lower, and more preferably 80° C. or lower.

[0124] The time for implementing the intermediate exposure (the time for exposing the precursor-attached graphite particles to the oxidizing gas atmosphere at the intermediate exposure temperature) is preferably 10 minutes or more, more preferably 20 minutes or more, and further preferably 30 minutes or more. The upper limit is not particularly limited, for example, 120 minutes, preferably 90 minutes, and more preferably 60 minutes.

[0125] 《Second Firing》

[0126] In the second calcination, the precursor-adhered graphite particles subjected to the intermediate exposure are heated at a temperature of 1100° C. to 1500° C. (hereinafter also referred to as “second calcination temperature”) in a non-oxidizing gas atmosphere.

[0127] The reason why the gas atmosphere of the second calcination is a non-oxidizing gas atmosphere and the preferred example of the non-oxidizing gas atmosphere are the same as those of the first calcination.

[0128] The second calcination temperature is 1100° C. or higher, preferably 1150° C. or higher, and more preferably 1200° C. or higher. The second calcination temperature is preferably equal to or higher than the first calcination temperature.

[0129] On the other hand, the second sintering temperature is 1500°C or lower, preferably 1400°C or lower, and more preferably 1300°C or lower.

[0130] The time for implementing the second calcination (the time for heating the precursor attached graphite particles at the second calcination temperature in a non-oxidizing gas atmosphere) is preferably 0.5 hours or more, more preferably 1 hour or more, and further preferably 2 hours or more. The upper limit is not particularly limited, for example, 30 hours, preferably 10 hours, and more preferably 5 hours.

[0131] [Negative electrode for lithium-ion secondary battery (negative electrode)]

[0132] The negative electrode for lithium ion secondary battery of the present embodiment contains the above-mentioned carbonaceous coated graphite particles. Hereinafter, the "carbonaceous coated graphite particles" are sometimes referred to as "negative electrode materials". In addition, the negative electrode for lithium ion secondary battery is sometimes simply referred to as "negative electrode".

[0133] The negative electrode of this embodiment is produced in accordance with a common negative electrode.

[0134] When manufacturing the negative electrode, it is preferred to add a binder to the negative electrode material and use a previously prepared negative electrode mixture. The negative electrode mixture may contain an active material other than the negative electrode material and a conductive material.

[0135] The binder preferably exhibits chemical stability and electrochemical stability to the electrolyte. For example, fluorine-based resins such as polytetrafluoroethylene and polyvinylidene fluoride; resins such as polyethylene, polyvinyl alcohol, and styrene-butadiene rubber; and carboxymethyl cellulose can be used. Two or more of these can also be used in combination.

[0136] The binder is usually used in a ratio of about 1 to 20% by mass based on the total amount of the negative electrode mixture.

[0137] More specifically, first, the negative electrode material is adjusted to a desired particle size by arbitrarily classifying or the like. Then, the negative electrode material is mixed with a binder, and the obtained mixture is dispersed in a solvent to prepare a paste-like negative electrode mixture. Examples of the solvent include water, isopropanol, N-methylpyrrolidone, dimethylformamide, and the like. For mixing and dispersing, a known stirrer, mixer, kneader, and the like can be used.

[0138] The prepared paste is applied to one or both sides of the current collector and dried. The coating amount is preferably 3 to 15 mg / cm 2 , more preferably 5 to 15 mg / cm 2 Thus, a negative electrode mixture layer (negative electrode) that is uniformly and firmly bonded to the current collector can be obtained. The thickness of the negative electrode mixture layer is preferably 10 to 200 μm, and more preferably 20 to 100 μm.

[0139] By performing compression bonding such as pressing and pressing after the negative electrode mixture layer is formed, the adhesion strength between the negative electrode mixture layer (negative electrode) and the current collector can be further increased.

[0140] The shape of the current collector is not particularly limited, and may be, for example, foil, mesh, or mesh such as expanded metal. The material of the current collector is preferably copper, stainless steel, nickel, etc. The thickness of the current collector in the case of foil is preferably about 5 to 20 μm.

[0141] 〈Coating electrode density〉

[0142] In the negative electrode of this embodiment, the coating electrode density is preferably 1.10 g / cm 3 More preferably, 1.20 g / cm 3 On the other hand, it is preferably 2.00 g / cm 3 Below, more preferably 1.90 g / cm 3 the following.

[0143] The coating electrode density of the negative electrode was determined as follows.

[0144] The mass (using an electronic balance) and thickness (using a micrometer) of the negative electrode punched into a certain area are measured. Next, the mass of 10 pieces of collectors punched into the same area are measured, and the average value is used as the mass of the collector. Further, the thickness of the collector is calculated based on the density of the metal of the collector. Then, the coated electrode density of the negative electrode is calculated by the following formula.

[0145] Negative electrode coating density = (negative electrode mass - collector mass) / (negative electrode thickness - collector thickness) × (punching area)

[0146] [Lithium-ion secondary battery]

[0147] The lithium ion secondary battery of the present embodiment includes the negative electrode of the present embodiment, and further includes a positive electrode, a nonaqueous electrolyte, and the like.

[0148] The lithium ion secondary battery of the present embodiment can be constructed by, for example, stacking a negative electrode, a nonaqueous electrolyte, and a positive electrode in this order and housing them in an exterior material.

[0149] The form of the lithium ion secondary battery of the present embodiment can be arbitrarily selected from cylindrical, rectangular, coin, button, and the like depending on the application, the device on which it is mounted, the required charge and discharge capacity, and the like.

[0150] <positive electrode>

[0151] The positive electrode material (positive electrode active material) is preferably a material that can absorb / desorb a sufficient amount of lithium. In addition to lithium, the positive electrode active material may include lithium-containing transition metal oxides, transition metal sulfide compounds, vanadium oxides and lithium compounds thereof; X Mo 6 S 8-Y (wherein M is at least one transition metal element, X is a value in the range of 0≤X≤4, and Y is a value in the range of 0≤Y≤1) represented by a Chevrel phase compound; activated carbon; activated carbon fiber; etc. Vanadium oxide is V 2 O 5 、V 6 O 13 、V 2 O 4 、V 3 O 8 express.

[0152] The lithium-containing transition metal oxide is a composite oxide of lithium and a transition metal, and may be a composite oxide in which lithium and two or more transition metals are solid-dissolved. The composite oxide may be used alone or in combination of two or more.

[0153] Lithium-containing transition metal oxides are specifically LiM 11-X M 2 X O 2 (Where M 1 、M 2 is at least one transition metal element, X is a value in the range of 0≤X≤1), or LiM 1 1-Y M 2 Y O 4 (Where M 1 、M 2 is at least one transition metal element, and Y is a numerical value in the range of 0≤Y≤1).

[0154] M 1 、M 2 The transition metal element represented by is Co, Ni, Mn, Cr, Ti, V, Fe, Zn, Al, In, Sn, etc., preferably Co, Fe, Mn, Ti, Cr, V, Al, etc. A preferred specific example is LiCoO 2 、LiNiO 2 、LiMnO 2 、LiNi 0.9 Co 0.1 O 2 、LiNi 0.5 Co 0.5 O 2 wait.

[0155] Lithium-containing transition metal oxides can be obtained, for example, by using lithium and transition metal oxides, hydroxides, salts, etc. as starting materials, mixing these starting materials according to the composition of the desired metal oxide, and calcining them at 600 to 1000° C. in an oxygen atmosphere.

[0156] The positive electrode active material may be the above-mentioned compound alone or in combination of two or more. For example, carbon salts such as lithium carbonate may be added to the positive electrode. When forming the positive electrode, various additives such as existing known conductive agents and binders may be appropriately used.

[0157] The positive electrode can be produced, for example, by applying a positive electrode mixture composed of a positive electrode active material, a binder, and a conductive agent for imparting conductivity to the positive electrode on both surfaces of a current collector to form a positive electrode mixture layer.

[0158] As the binder, a binder used in the production of the negative electrode can be used.

[0159] As the conductive agent, known conductive agents such as graphite and carbon black can be used.

[0160] The shape of the current collector is not particularly limited, and examples thereof include foil and mesh. The material of the current collector is aluminum, stainless steel, nickel, etc. The thickness of the current collector is preferably 10 to 40 μm.

[0161] For the positive electrode, similarly to the negative electrode, a paste of positive electrode mixture may be applied to a current collector and dried, followed by compression bonding such as pressing.

[0162] 〈Non-aqueous electrolytes〉

[0163] The nonaqueous electrolyte may be a liquid nonaqueous electrolyte (nonaqueous electrolyte solution), or may be a polymer electrolyte such as a solid electrolyte or a gel electrolyte.

[0164] As the non-aqueous electrolyte, LiPF, which is an electrolyte salt used in a general non-aqueous electrolyte solution, can be used. 6 , LiBF 4 、LiAsF 6 、LiClO 4 、LiB(C 6 H 5 )、LiCl、LiBr、LiCF 3 SO 3 、LiCH 3 SO 3 、LiN(CF 3 SO 2 ) 2 、LiC(CF 3 SO 2 ) 3 、LiN(CF 3 CH 2 OSO 2 ) 2 、LiN(CF 3 CF 2 OSO 2 ) 2 、LiN(HCF 2 CF 2 CH 2 OSO 2 ) 2 、LiN((CF 3 ) 2 CHOSO 2 ) 2 、LiB[{C 6 H 3 (CF 3 ) 2}] 4 、LiAlCl 4 、LiSiF 6 From the perspective of oxidation stability, LiPF6 , LiBF 4 .

[0165] The concentration of the electrolyte salt in the nonaqueous electrolyte solution is preferably 0.1 to 5.0 mol / L, more preferably 0.5 to 3.0 mol / L.

[0166] Examples of the solvent used to prepare the non-aqueous electrolyte solution include carbonates such as ethylene carbonate, propylene carbonate, dimethyl carbonate, and diethyl carbonate; ethers such as 1,1- or 1,2-dimethoxyethane, 1,2-diethoxyethane, tetrahydrofuran, 2-methyltetrahydrofuran, γ-butyrolactone, 1,3-dioxolane, 4-methyl-1,3-dioxolane, anisole, and diethyl ether; sulfides such as sulfolane and methyl sulfolane; nitriles such as acetonitrile, chloronitrile, and propionitrile; trimethyl borate, tetramethyl silicate, nitromethane, dimethylformamide, N-methylpyrrolidone, ethyl acetate, trimethyl orthoformate, nitrobenzene, benzoyl chloride, benzoyl bromide, tetrahydrothiophene, dimethyl sulfoxide, 3-methyl-2- Aprotic organic solvents such as oxazolidinone, ethylene glycol, dimethyl sulfite, etc.

[0167] When the nonaqueous electrolyte is a polymer electrolyte such as a solid electrolyte or a gel electrolyte, it is preferable to use a polymer gelled with a plasticizer (nonaqueous electrolyte solution) as a matrix.

[0168] As the polymer constituting the matrix, ether polymer compounds such as polyoxyethylene and crosslinked products thereof; poly(meth)acrylate polymer compounds; fluorine polymer compounds such as polyvinylidene fluoride and vinylidene fluoride-hexafluoropropylene copolymers, etc. can be suitably used.

[0169] The concentration of the electrolyte salt in the nonaqueous electrolyte solution as a plasticizer is preferably 0.1 to 5.0 mol / L, more preferably 0.5 to 2.0 mol / L.

[0170] In the polymer electrolyte, the proportion of the plasticizer is preferably 10 to 90% by mass, more preferably 30 to 80% by mass.

[0171] 〈Partition〉

[0172] A separator may also be used in the lithium ion secondary battery of this embodiment.

[0173] The material of the separator is not particularly limited, for example, woven fabric, nonwoven fabric, synthetic resin microporous film, etc. can be used. Among them, preferably a synthetic resin microporous film, wherein, from the aspect of thickness, film strength, and film resistance, a polyolefin microporous film is more preferably used. As the polyolefin microporous film, preferably a polyethylene microporous film, a polypropylene microporous film, a microporous film composited therefrom, etc. can be mentioned.

[0174] Example

[0175] Hereinafter, the present invention will be specifically described with reference to Examples. However, the present invention is not limited to the Examples described below.

[0176] <Example 1>

[0177] 《Preparation of graphite particles》

[0178] The flaky natural graphite (particle size: 8 μm) as a raw material was continuously passed through 5 pulverizers (Hybridization System, manufactured by Nara Machinery Manufacturing Co., Ltd.) arranged in series. In each pulverizer, the pulverization time was set to 30 minutes and the circumferential speed of the rotor was set to 50 m / s. Thus, graphite particles as spherical graphite were obtained by pulverizing and granulating the raw material.

[0179] 《Preparation of Precursor-Attached Graphite Particles》

[0180] The pulverized phenolic resin, i.e., carbonaceous precursor, is added to the obtained graphite particles (spheroidized graphite) and mixed at room temperature for 30 minutes using a twin-screw kneader. The carbonaceous precursor of the amount of 4.0 mass % is added. Thus, the precursor attached graphite particles with the carbonaceous precursor (phenolic resin) attached to the surface of the graphite particles (spheroidized graphite) are obtained.

[0181] 《Preparation of Carbon-Coated Graphite Particles》

[0182] Next, the obtained precursor-adhered graphite particles were fired using a tubular furnace (first firing, intermediate exposure, and second firing).

[0183] Specifically, first, in the first sintering, a gas atmosphere (non-oxidizing gas atmosphere) in which nitrogen flows at 5 L / min is set, and then the precursor-attached graphite particles are heated at a first sintering temperature of 950° C. for 60 minutes, and then cooled to the intermediate exposure temperature described later without changing the gas atmosphere.

[0184] Next, in the intermediate exposure, the cooled precursor-attached graphite particles were exposed to an air atmosphere (oxidizing gas atmosphere) at an intermediate exposure temperature of 80° C. for 30 minutes.

[0185] Then, in the second calcination, after setting the gas atmosphere to flow nitrogen at 2 L / min (non-oxidizing gas atmosphere), the precursor-attached graphite particles were heated at the second calcination temperature of 1100° C. for 60 minutes.

[0186] As a result, the carbonaceous precursor (phenol resin) becomes carbonaceous, and carbonaceous-coated graphite particles in which the surfaces of graphite particles (spheroidized graphite) are coated with carbonaceous are obtained.

[0187] The physical properties of the obtained carbonaceous coated graphite particles were determined by the above-mentioned methods. The results are shown in Table 1 below.

[0188] The Making of Negative Electrode

[0189] 98 parts by mass of carbonaceous coated graphite particles (negative electrode material), 1 part by mass of carboxymethyl cellulose (binder), and 1 part by mass of styrene-butadiene rubber (binder) were added to water and stirred to prepare a negative electrode mixture paste.

[0190] The prepared negative electrode mixture paste was applied to a copper foil (thickness: 16 μm) with a uniform thickness, and further dried at 90°C in a vacuum to form a negative electrode mixture layer. Next, the negative electrode mixture layer was pressurized at a pressure of 120 MPa using a manual press. Then, the copper foil and the negative electrode mixture layer were punched into a circular shape with a diameter of 15.5 mm. In this way, a negative electrode (thickness: 60 μm, coating electrode density: 1.20 g / cm 3 ).

[0191] The Making of Positive Electrode

[0192] The lithium metal foil was pressed against a nickel mesh and punched into a circular shape with a diameter of 15.5 mm. In this way, a positive electrode composed of a lithium metal foil (thickness: 0.5 mm) in close contact with a current collector composed of the nickel mesh was prepared.

[0193] 《Evaluating the production of batteries》

[0194] As an evaluation battery, Figure 1 The button-type secondary battery shown.

[0195] Figure 1 is a cross-sectional view showing a button-type secondary battery. Figure 1 In the button-type secondary battery shown, the outer cup 1 and the outer can 3 are riveted to form a sealed structure with an insulating gasket 6 interposed therebetween. Inside the sealed structure, the collector 7a, the positive electrode 4, the separator 5, the negative electrode 2, and the collector 7b are stacked in order from the inner surface of the outer can 3 to the inner surface of the outer cup 1.

[0196] The following was produced Figure 1 The button-type secondary battery shown.

[0197] First, LiPF was added at a concentration of 1 mol / L. 6 The nonaqueous electrolyte solution was prepared by dissolving it in a mixed solvent of ethylene carbonate (33% by volume) and ethyl methyl carbonate (67% by volume), and the separator 5 impregnated with the nonaqueous electrolyte solution was prepared by impregnating the obtained nonaqueous electrolyte solution into a polypropylene porous body (thickness: 20 μm).

[0198] Next, the prepared separator 5 is sandwiched between the negative electrode 2 which is closely attached to the current collector 7b made of copper foil and the positive electrode 4 which is closely attached to the current collector 7a made of nickel mesh, and the layers are stacked. Then, the current collector 7b and the negative electrode 2 are accommodated in the outer cup 1, the current collector 7a and the positive electrode 4 are accommodated in the outer can 3, and the outer cup 1 and the outer can 3 are joined. Furthermore, the outer cup 1 and the outer can 3 are sealed by riveting the peripheral portions thereof with the insulating gasket 6 interposed therebetween. Thus, a button-type secondary battery is manufactured.

[0199] The produced button-type secondary battery (evaluation battery) was used to carry out the test described below to evaluate the battery characteristics. The results are shown in Table 1 below.

[0200] In the following tests, the process of absorbing lithium ions into the negative electrode material is called charging, and the process of desorbing lithium ions from the negative electrode material is called discharging.

[0201] 《Test 1: Discharge capacity and initial charge and discharge efficiency (initial charge and discharge characteristics)》

[0202] First, a constant current charge is performed at a current value of 0.9mA until the circuit voltage reaches 0mV. When the circuit voltage reaches 0mV, it is switched to constant voltage charging, and the charging is continued until the current value reaches 20μA. The charge capacity (monomer: mAh) is calculated based on the amount of power supplied during this period. Then, stop for 120 minutes. Next, a constant current discharge is performed at a current value of 0.9mA until the circuit voltage reaches 1.5V. The discharge capacity (monomer: mAh) is calculated based on the amount of power supplied during this period. This is regarded as the first cycle.

[0203] The initial charge and discharge efficiency (monomer: %) was calculated based on the following formula from the charge capacity and discharge capacity in the first cycle. The results are shown in the following Table 1. The larger the value, the better the initial charge and discharge characteristics can be evaluated.

[0204] Initial charge and discharge efficiency = (discharge capacity / charge capacity) × 100

[0205] 《Test 2: 25℃ Input Resistivity (Input Characteristics)》

[0206] In a temperature atmosphere of 25° C., constant current charging was performed at 1.0 C until the circuit voltage reached 3.82 V. Then, the temperature of the gas atmosphere was adjusted to 0° C. and the battery was left idle for 3 hours.

[0207] Next, the battery was charged at 0.5C for 10 seconds and then rested for 10 minutes, and then discharged at 0.5C for 10 seconds and then rested for 10 minutes.

[0208] Next, the battery was charged at 1.0 C for 10 seconds, rested for 10 minutes, discharged at 0.5 C for 20 seconds, the SOC (State of Charge) was set to 50%, and rested for 10 minutes.

[0209] Next, the battery was charged at 1.5 C for 10 seconds, then rested for 10 minutes, and then discharged at 0.5 C for 30 seconds to set the SOC to 50%, followed by a rest period of 10 minutes.

[0210] Next, the battery was charged at 2.0 C for 10 seconds, then rested for 10 minutes, and then discharged at 0.5 C for 40 seconds to set the SOC to 50%, followed by a rest period of 10 minutes.

[0211] The current value was calculated by multiplying the discharge capacity (single cell: mAh) obtained in Test 1 by each C rate (0.5C, 1.0C, 1.5C, 2.0C). In addition, the voltage (10-second value) when charging at the C rate was obtained.

[0212] The current value is used as the x-coordinate and the voltage is used as the y-coordinate. The results at each C rate are plotted and the slope of their linear approximation line is calculated by the least squares method. The slope is used as the input resistance (single unit: Ω). The smaller the value, the better the input characteristics can be evaluated.

[0213] Furthermore, the relative value (ratio) of the input resistance of each example to the input resistance of Example 1 was obtained from the following formula, and the relative value (ratio) was defined as the input resistivity at 25° C. The results are shown in Table 1 below.

[0214] 25°C input resistivity = (input resistance of each example / input resistance of Example 1) × 100

[0215] 《Test 3: 45℃ Cycle Durability (Cycle Capacity Retention)》

[0216] In a 45°C temperature atmosphere, constant current charging was performed at 0.5 C until the circuit voltage reached 4.1 V. Then, the battery was rested for 10 minutes.

[0217] Next, the battery was discharged at 0.5C until the circuit voltage reached 2.5V, and then rested for 10 minutes.

[0218] Such charge and discharge were repeated 100 times in total, and the ratio of the 100th discharge capacity to the first discharge capacity (45° C. cycle durability, single body: %) was calculated.

[0219] The results are shown in the following Table 1. The larger the value, the more excellent the cycle capacity retention can be evaluated.

[0220] <Example 2>

[0221] Carbonaceous coated graphite particles were prepared and evaluated in the same manner as in Example 1 except that the amount of the carbonaceous precursor added was changed to an amount such that the carbonaceous content finally obtained would be 5.0 mass %. The results are shown in Table 1 below.

[0222] <Example 3>

[0223] Carbonaceous coated graphite particles were prepared and evaluated in the same manner as in Example 1 except that the amount of the carbonaceous precursor added was changed to an amount such that the carbonaceous content finally obtained would be 6.0% by mass. The results are shown in Table 1 below.

[0224] <Example 4>

[0225] Carbonaceous coated graphite particles were prepared and evaluated in the same manner as in Example 2 except that the time for performing the intermediate exposure was changed to 10 minutes. The results are shown in Table 1 below.

[0226] <Example 5>

[0227] Carbonaceous coated graphite particles were prepared and evaluated in the same manner as in Example 2 except that the first calcination temperature was changed to 1000° C. The results are shown in Table 1 below.

[0228] <Example 6>

[0229] Carbonaceous coated graphite particles were prepared and evaluated in the same manner as in Example 1 except that the intermediate exposure temperature was 60° C. The results are shown in Table 1 below.

[0230] <Comparative Example 1>

[0231] In Comparative Example 1, the carbonaceous precursor (phenol resin) was not attached to the graphite particles (spheroidized graphite), and only the graphite particles (spheroidized graphite) were calcined in the same manner as in Example 5 (first calcination, intermediate exposure, and second calcination).

[0232] <Comparative Example 2>

[0233] 《Preparation of graphite particles》

[0234] In the same manner as in Example 1, graphite particles as spheroidized graphite were obtained.

[0235] 《Preparation of Precursor-Attached Graphite Particles》

[0236] In the same manner as in Example 1, precursor-attached graphite particles were obtained in which a carbonaceous precursor (phenol resin) was attached to the surface of graphite particles (spheroidized graphite).

[0237] 《Preparation of Carbon-Coated Graphite Particles》

[0238] The obtained precursor-adhered graphite particles were placed in a graphite container with a lid and fired using a tubular furnace.

[0239] Specifically, first, a gas atmosphere (non-oxidizing gas atmosphere) in which nitrogen was flowed at 2 L / min was set, and then the precursor-attached graphite particles were heated at a first calcination temperature of 950° C. for 60 minutes.

[0240] Next, without cooling (intermediate exposure), heating was performed at a second calcination temperature of 1100° C. for 60 minutes in a gas atmosphere (non-oxidizing gas atmosphere) in which nitrogen was flowed at 2 L / min.

[0241] As a result, the carbonaceous precursor (phenol resin) becomes carbonaceous, and carbonaceous-coated graphite particles in which the surfaces of graphite particles (spheroidized graphite) are coated with carbonaceous are obtained.

[0242] The physical properties of the obtained carbonaceous coated graphite particles were determined by the above-mentioned methods. The results are shown in Table 1 below.

[0243] <Comparative Example 3>

[0244] 《Preparation of graphite particles》

[0245] In the same manner as in Example 1, graphite particles as spheroidized graphite were obtained.

[0246] 《Preparation of Precursor-Attached Graphite Particles》

[0247] In the same manner as in Example 1, precursor-attached graphite particles were obtained in which a carbonaceous precursor (phenol resin) was attached to the surface of graphite particles (spheroidized graphite).

[0248] 《Preparation of Carbon-Coated Graphite Particles》

[0249] The obtained precursor-adhered graphite particles were placed in a graphite container with a lid and fired using a tubular furnace.

[0250] Specifically, after setting the gas atmosphere (non-oxidizing gas atmosphere) in which nitrogen was flowed at 2 L / min, the precursor-attached graphite particles were heated at a calcining temperature of 1100° C. for 60 minutes.

[0251] As a result, the carbonaceous precursor (phenol resin) becomes carbonaceous, and carbonaceous-coated graphite particles in which the surfaces of graphite particles (spheroidized graphite) are coated with carbonaceous are obtained.

[0252] The physical properties of the obtained carbonaceous coated graphite particles were determined by the above-mentioned methods. The results are shown in Table 1 below.

[0253] <Comparative Example 4>

[0254] 《Preparation of graphite particles》

[0255] In the same manner as in Example 1, graphite particles as spheroidized graphite were obtained.

[0256] 《Preparation of Precursor-Attached Graphite Particles》

[0257] Precursor-attached graphite particles in which a carbonaceous precursor (phenol resin) was attached to the surface of graphite particles (spheroidized graphite) were obtained in the same manner as in Example 1 so that the carbonaceous content in the finally obtained carbonaceous coated graphite particles was 2.0 parts by mass.

[0258] 《Preparation of Carbon-Coated Graphite Particles》

[0259] The obtained precursor-adhered graphite particles were placed in a graphite container with a lid and fired using a tubular furnace.

[0260] Specifically, first, the first calcination was carried out in the same manner as in Example 1.

[0261] Then, intermediate exposure was carried out in the same manner as in Example 1 to obtain an intermediate exposure body.

[0262] Then, the second carbonaceous precursor was attached. More specifically, the phenolic resin was attached to the intermediate exposure body under the same conditions as in the "Preparation of Precursor-Attached Graphite Particles" of Example 1. At this time, the phenolic resin was attached in such a manner that the carbon content in the finally obtained carbonaceous coated graphite particles reached 2.0 parts by mass.

[0263] Finally, the second calcination was carried out in the same manner as in Example 1.

[0264] Thus, the carbonaceous precursor (phenol resin) became carbonaceous, and carbonaceous-coated graphite particles in which the surfaces of graphite particles (spheroidized graphite) were coated with carbonaceous materials were obtained. The carbonaceous content in the obtained carbonaceous-coated graphite particles was 4.0% by mass.

[0265] The physical properties of the obtained carbonaceous coated graphite particles were determined by the above-mentioned methods. The results are shown in Table 1 below.

[0266]

[0267] 〈Summary of evaluation results〉

[0268] As shown in Table 1, Examples 1 to 6 having carbonaceous coated graphite particles and an elastic modulus of 10 GPa or more have better cycle capacity retention than Comparative Examples 1 to 4 that do not meet these conditions. In addition, Examples 1 to 6 also have good initial charge and discharge characteristics and input characteristics.

Claims

1. A carbonaceous coated graphite particle, comprising: Graphite particles, and a carbonaceous material covering at least a portion of the surface of the graphite particle, The carbonaceous coated graphite particles have an elastic modulus of 10 GPa or more as determined using a scanning probe microscope.

2. The carbonaceous coated graphite particles according to claim 1, wherein the particle size is 5.0 to 15.0 μm and the specific surface area is 3.0 to 15.0 m 2 / g.

3. The carbonaceous coated graphite particles according to claim 1, wherein The content of the carbonaceous material is 1.0 to 30.0% by mass relative to the total mass of the carbonaceous coated graphite particles. 4 . The carbonaceous coated graphite particles according to claim 1 , which are a negative electrode material for a lithium ion secondary battery. 5 . A negative electrode for a lithium ion secondary battery, comprising the carbonaceous coated graphite particles according to claim 1 . 6 . A lithium ion secondary battery comprising the negative electrode according to claim 5 .

7. A method for producing carbonaceous coated graphite particles, which is a method for producing the carbonaceous coated graphite particles according to any one of claims 1 to 3, the method comprising: making a carbonaceous precursor, which is a precursor of the carbonaceous material, adhere to the graphite particles to obtain precursor-attached graphite particles, A first calcination step is performed in which the precursor-attached graphite particles are heated at a temperature exceeding 900° C. and not more than 1500° C. in a non-oxidizing gas atmosphere. After the first calcination, an intermediate exposure is performed in which the precursor-attached graphite particles are exposed to an oxidizing gas atmosphere at a temperature of 50 to 100° C., After the intermediate exposure, a second calcination is performed in which the precursor-attached graphite particles are heated at a temperature of 1100 to 1500° C. in a non-oxidizing gas atmosphere.

Citation Information

Patent Citations

  • Carbon material for lithium ion secondary battery

    JP2014146607A